Sedimentological and Micropaleontological Characteristics of the Black Clay Deposit of the Baturetno Formation, Wonogiri, Central Java - Putra, Purna Sulastya; Yulianto, Eko (Indonesian Journal on Geoscience, 2016)
DOI:10.17014/ijog.3.3.163-171A previous research on black clay of the Baturetno Formation identified that this clay was a palaeolake deposit. In this study, the black clay deposit was characterized by using sedimentological and micropaleontological approaches to reveal its origin. The black clay of the Baturetno Formation has a low organic matter (mostly less than 8%) and almost no pollen content. These characteristics are not representative of a lake deposit. This black clay was suggested a mud flow deposit. This conclusion is supported by the occurrence of dispersed rock fragments in the clay deposit. In addition, the previous research has identified that the formation of a palaeolake was related to the Late Pliocene tilting in South Java. The carbon dating indicates that the deposition of this clay has no relationship to the Late Pliocene tilting in South Java as the age of this clay was determined to be much younger (around 7000 BP; early Holocene).